Route of inoculation and mosquito vector exposure modulate dengue virus replication kinetics and immune responses in rhesus macaques. - Michael K McCracken; Gregory D Gromowski; Lindsey S Garver; Brad A Goupil; Kathryne D Walker; Heather Friberg; Jeffrey R Currier; Wiriya Rutvisuttinunt; Kevin L Hinton; Rebecca C Christofferson; Christopher N Mores; Yannick Vanloubbeeck; et al. (Public Library of Science (PLoS), 2020)
Dengue virus (DENV) is transmitted by infectious mosquitoes during blood-feeding via saliva containing biologically-active proteins. Here, we examined the effect of varying DENV infection modality in rhesus macaques in order to improve the DENV nonhuman primate (NHP) challenge model. NHPs were exposed to DENV-1 via subcutaneous or intradermal inoculation of virus only, intradermal inoculation of virus and salivary gland extract, or infectious mosquito feeding. The infectious mosquito feeding group exhibited delayed onset of viremia, greater viral loads, and altered clinical and immune responses compared to other groups. After 15 months, NHPs in the subcutaneous and infectious mosquito feeding groups were re-exposed to either DENV-1 or DENV-2. Viral replication and neutralizing antibody following homologous challenge were suggestive of sterilizing immunity, whereas heterologous challenge resulted in productive, yet reduced, DENV-2 replication and boosted neutralizing antibody. These results show that a more transmission-relevant exposure modality resulted in viral replication closer to that observed in humans.